SAR towards indoline and 3-azaindoline classes of IDO1 inhibitors. (1st September 2021) - Yu, Wensheng; Deng, Yongqi; Hopkins, Brett; Huang, Xianhai; Sloman, David; Zhang, Hongjun; Li, Derun; McGowan, Meredeth A.; White, Catherine; Pu, Qinglin; Liu, Kun; Fradera, Xavier; et al.
Graphical abstract: Abstract: A novel series of IDO1 inhibitors have been identified with good IDO1 Hela cell and human whole blood activity. These inhibitors contain an indoline or a 3-azaindoline scaffold. Their structure-activity-relationship studies have been explored. Compounds 37 and 41 stood out as leads due to their good potency in IDO1 Hela assay, good IDO1 unbound hWB IC50 s, reasonable unbound clearance, and good MRT in rat and dog PK studies.